Research on the influence of anchor characteristics on consumer purchase intention—a case study of selected anchors on Dong Yuhui’s “With Hui” Live-stream account - Li, Ruiqiang; Cui, Yaoyuan; Mei, Xue (Frontiers in Communication, 2025)
Based on previous research and combined with the S-O-R theoretical model, this study examines the characteristics of anchors on Dong Yuhui’s “With Hui” Live-stream account as independent variables. The characteristics, measured by professionalism, high interactivity, fame, and attractiveness, are analyzed to determine their impact on consumer purchase intention. Perceived trust is set as a mediating variable, anticipated regret as a moderating variable, and purchase intention as the dependent variable to construct a model for reference by anchors on Dong Yuhui’s “With Hui” Live-stream account. Results show that anchor characteristics significantly and positively influence purchase intention; professionalism, high interactivity, fame, and attractiveness all have a notable positive impact on purchase intention. And anchor characteristics significantly and positively impact perceived trust, with professionalism, high interactivity, fame, and attractiveness positively influencing perceived trust. Perceived trust positively affects purchase intention and perceived trust partially mediates the relationship between anchor characteristics and purchase intention, with partial mediation observed between professionalism, high interactivity, fame, and attractiveness on purchase intention. Anticipated regret moderates the relationship between perceived trust and purchase intention, with upward anticipated regret showing a negative moderating effect, while downward anticipated regret shows a positive moderating effect on the perceived trust-purchase intention relationship.